2021
DOI: 10.3390/catal11111365
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Methyl Mercaptan on Mesoporous Alumina Prepared with Hydroxysafflor Yellow A as Template: The Synergistic Effect of Potassium and Molybdenum

Abstract: K-promoted Mo-based catalysts showed great promise for the hydrogenation of CS2 to methyl mercaptan (CH3SH). However, the research on the synergistic effect of K and Mo, and the active site of CS2 hydrogenation to CH3SH were unexplored widely. To solve this problem, the synergistic effect of K and Mo in the K-promoted Mo-based catalysts for CS2 hydrogenation to prepare CH3SH was investigated. The mesoporous alumina was the support and loaded the active components potassium and molybdenum to prepare the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Methyl mercaptan from CS 2 and COS. As shown above, CS 2 and COS are key intermediates in the CH 3 SH synthesis from syngas and H 2 S. Therefore, some research groups used CS 2 and COS as raw materials to produce CH 3 SH, according to eqn (3) and (4). [68][69][70][98][99][100][101][102][103][104] Both reactions are fast and thermodynamically allowed under industrial conditions. 68 CS 2 + 3H 2 → CH 3 SH + H 2 S…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Methyl mercaptan from CS 2 and COS. As shown above, CS 2 and COS are key intermediates in the CH 3 SH synthesis from syngas and H 2 S. Therefore, some research groups used CS 2 and COS as raw materials to produce CH 3 SH, according to eqn (3) and (4). [68][69][70][98][99][100][101][102][103][104] Both reactions are fast and thermodynamically allowed under industrial conditions. 68 CS 2 + 3H 2 → CH 3 SH + H 2 S…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…As shown above, CS 2 and COS are key intermediates in the CH 3 SH synthesis from syngas and H 2 S. Therefore, some research groups used CS 2 and COS as raw materials to produce CH 3 SH, according to eqn (3) and (4). 68–70,98–104 Both reactions are fast and thermodynamically allowed under industrial conditions. 68 CS 2 + 3H 2 → CH 3 SH + H 2 SCOS + 3H 2 ↔ CH 3 SH + H 2 O Δ H = 124 kJ mol −1 In one of the earlier studies, Kubicek 98 showed that CH 3 SH can be obtained from CS 2 over the Co–Mo/Al 2 O 3 catalyst, at 200–300 °C and 3.9 MPa.…”
Section: Production Of Methyl Mercaptanmentioning
confidence: 99%
See 1 more Smart Citation